Evaluation of Pharmacognostic Characteristics of the Leaf of Ageratum houstonianum Mill. Compositae (Nigerian Journal of Pharmaceutical Research, 2020)
Background: It is a well-known fact that therapeutic efficacy and safety of medicinal plants depend on the quality and quantity of chemical constituents and that the misuse of medicinal plants starts with wrong identification.Objectives: The aim of this study is to establish some pharmacognostic standards for Ageratum houstonianum Mill (Compositae) which has high medicinal values, with a view to determining the proper identification and other quality control parameters of the plant.Method: The fresh leaf and powdered leaves were subjected to macroscopy and microscopy using standard procedures. In addition, some physicochemical evaluations such as moisture content, ash and soluble extractives were carried out on the powdered leaves.Results: The result shows that the leaf is simple, pinnate, diamond shaped, serrated margin, acute apex and asymetrical base. Microscopically, the leaf is amphistomatic in nature with anomocytic and anisocytic stomata at the adaxial and anomocytic and diacytic at the abaxial surface. Non-glandular uniseriate trichomes are present on both surfaces. The transverse section across the midrib shows epidermis, collenchyma, palisade cells and a few rolls of phloem around the xylem vessels. The stomata numbers and stomata indices for the upper and lower surface, respectively are1.4 and 10.2 and 2.9 and 15.6. Moisture content, total ash, acid insoluble ash, water soluble ash, sulphated ash, water soluble and alcohol soluble extractives yields 10.3%, 15.2%, 0.8%, 20.2%, 14.4% and 5.1%, respectively.Conclusion: The findings in this study are useful for establishing standards suitable for official monographs on Ageratum houstonianum proper identification and quality control.
Keywords: Pharmacognostic standards; Ageratum houstonianum; Quality control